2020
DOI: 10.1097/aln.0000000000002959
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Accumulation and Phenotype Assessments of Frailty Both Poorly Predict Duration of Hospitalization and Serious Complications after Noncardiac Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Frailty is associated with adverse postoperative outcomes, but it remains unclear which measure of frailty is best. This study compared two approaches: the Modified Frailty Index, which is a deficit accumulation model (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Indeed, of routinely collected outcomes, hospital length of stay has arguably the highest variation and most substantial contribution from indirect patient predictors (e.g., social status, home supports, availability of allied health services). Neither of the frailty instruments tested by Sonny et al 1 capture these factors and are therefore unlikely to accurately predict or explain a substantial degree of variance in prolongation of stay.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, of routinely collected outcomes, hospital length of stay has arguably the highest variation and most substantial contribution from indirect patient predictors (e.g., social status, home supports, availability of allied health services). Neither of the frailty instruments tested by Sonny et al 1 capture these factors and are therefore unlikely to accurately predict or explain a substantial degree of variance in prolongation of stay.…”
mentioning
confidence: 97%
“…While we agree that a dichotomized frailty assignment is often used for risk stratification, if the objective of a study is to determine the predictive accuracy of a given scale, it is well demonstrated that dichotomization of a predictor variable can lead to decreased predictive performance compared to continuous representations such as regression splines or polynomials. 7 Last, and perhaps most salient to the study by Sonny et al, 1 type of surgery is likely the most important predictor of complications and length of stay. While the study's primary outcome, prolonged length of stay, was determined based on the difference between actual length of stay and hospitaland surgery-specific expected length of stay (which provides some degree of procedural adjustment), this approach may also downwardly bias measures of accuracy.…”
mentioning
confidence: 98%
See 3 more Smart Citations